2022-RA-631-ESGO The impact of COVID 19 on cervical cancer screening and triage. (20th October 2022) - Velasquez, Jessica M; Papatla, Katyayani; Kaplowitz, Elianna; Coughlin, Arielle C; Zachem, Alexis L; Goldberger, Cody; Blank, Stephianie V
Abstract : Introduction/Background: Prior studies have demonstrated decreased rates of cervical cancer (CC) screening during the height of the COVID-19 pandemic. Delayed CC screening and management may increase incidence and mortality. This study examines the impact of the COVID-19 pandemic on rates of guideline-indicated colposcopy. Methodology: This study used retrospective data from a large, urban, academic institution-based clinic comprised of publicly-insured patients. Patients were non-pregnant, 21 to 65 years old without HIV or other immunocompromise. Three time periods were used: pre-COVID (pC) (3/1/2019–2/28/2020), COVID (C) (3/1/2020–2/28/2021), post-COVID vaccine (pv) (3/1/2021–2/28/2022). Primary outcomes were compared between groups using T-tests or Wilcoxon-Rank Sum tests for continuous measures and Chi-square or Fisher's exact tests for categorical measures. Results: N=486. The interval between pap smears significantly increased from a pC mean of 490 days, to a C mean of 607 days, to a pv mean of 670 days (p=0.0128). The proportion of patients who underwent guideline-indicated colposcopy did not differ significantly between time periods (p=0.0740). The interval between abnormal pap smear and colposcopy significantly decreased from 104 days pC (SD 69–188) to 67 days C (SD 42–147), to 57 days pv (SD 33–104) (p=0.0001). There were no significant differences in pap smear cytology, colposcopic pathology or rate of referral for excisional procedure over time. There was a significant increase in the percentage of patients being contacted regarding abnormal pap smear results, specifically by by MD providers from 43% pC, to 53% C, to 61.6% pv (P=0.0029). Conclusion: This study demonstrates an increased interval between pap smears; however, those patients undergoing screening had significantly decreased time from pap to colposcopy which may be secondary to increased MD-to-patient telehealth communication and optimization of systems during the pandemic when routine clinics were limited. Future studies are needed to assess long-term outcomes of delayed CC screening on incidence and mortality.